Functional characterization and evolution of the isotuberculosinol operon in Mycobacterium tuberculosis and related Mycobacteria - Peters, Reuben J.; Mann, Francis M.; Xu, Meimei; Davenport, Emily K. (Frontiers in Microbiology, 2012)
Terpenoid metabolites are important to the cellular function, structural integrity, and pathogenesis of the human-specific pathogen Mycobacterium tuberculosis (Mtb). Genetic and biochemical investigations have indicated a role for the diterpenoid isotuberculosinol (isoTb) early in the infection process. There are only two genes (Rv3377c and Rv3378c) required for production of isoTb, yet these are found in what appears to be a five-gene terpenoid/isoprenoid biosynthetic operon. Of the three remaining genes (Rv3379c, Rv3382c, and Rv3383c), previous work has indicated that Rv3379c is an inactive pseudo-gene. Here we demonstrate that Rv3382c and Rv3383c encode biochemically redundant machinery for isoprenoid metabolism, encoding a functional 4-hydroxy-3-methylbut-2-enyl diphosphate reductase (LytB) for isoprenoid precursor production and a geranylgeranyl diphosphate (GGPP) synthase, respectively, for which the Mtb genome contains other functional isozymes (Rv1110 and Rv0562, respectively). These results complete the characterization of the isoTb biosynthetic operon, as well as further elucidating isoprenoid metabolism in Mtb. In addition, we have investigated the evolutionary origin of this operon, revealing Mtb-specific conservation of the diterpene synthase genes responsible for isoTb biosynthesis, which supports our previously advanced hypothesis that isoTb acts as a human-specific pathogenic metabolite and is consistent with the human host specificity of Mtb. Intriguingly, our results revealed that many mycobacteria contain orthologs for both Rv3383c and Rv0562, suggesting a potentially important role for these functionally redundant GGPP synthases in the evolution of terpenoid/isoprenoid metabolism in the mycobacteria.